Effect of transcutaneous electrical acupoint stimulation on length of stay for patients after undergoing surgery for colorectal cancer: a systematic review and meta-analysis of randomized controlled trials - YaDan Xiao; Fei Yang; JunLiang Zhou; YuanLing Huang; YaXin Xiao (Frontiers in Medicine)
ObjectiveThis study aimed to examine the effect of transcutaneous electrical acupoint stimulation (TEAS) on the length of stay (LOS) of patients undergoing surgery for colorectal cancer.MethodsA systematic review was conducted by searching databases, including PubMed, Embase, Cochrane Library, China Network Knowledge Infrastructure, and Wanfang Database for randomized controlled trials (RCTs) published up to August 24, 2024. Statistical analyses were performed using the Cochrane Collaboration Review Manager (RevMan 5.4). The quality of the RCTs was assessed using the Cochrane Systematic Review Handbook 5.1 and its recommended risk-of-bias assessment tool. Two independent investigators screened and extracted the data and performed statistical analysis.ResultsSeven RCTs were included in the analysis. The findings indicated that TEAS significantly reduced the LOS of patients undergoing surgery for colorectal cancer (mean difference = −1.36, 95% confidence interval = −1.95 to −0.78, p < 0.00001). Subgroup analyses of outcome measures, intervention methods, and intervention time points demonstrate the significant effect of TEAS on reducing LOS.ConclusionTEAS effectively shortens the LOS of patients undergoing surgery for colorectal cancer. Future studies should focus on refining TEAS protocols and exploring their effects on other aspects of postoperative recovery to fully establish their roles in perioperative management.